Young Adults' Online Sexual Health Information Seeking and Evaluating Skills: Implications for Everyday Life Information Literacy Instruction. Issue 1 (14th October 2022) - Behre, Jane
ABSTRACT: Many young adults (particularly LGBTQ+ young people) often do not receive relevant sexual health information in school‐based health education classes, leaving them with unmet information needs, which they largely go online in order to fulfill. Meanwhile, information literacy instruction is almost exclusively provided to young adults within an academic context; thus, the knowledge and skills they learn may not be easily adapted to everyday life contexts, including health. In order to learn more about this potential mismatch and to identify potential ways in which we might improve information literacy instruction for this population, I conducted an online survey incorporating LGBTQ+ inclusive language. The results suggest that the most popular online health information evaluation strategies amongst young adults may be unreliable and, while this population may understand more reliable methods, they appear to struggle to apply these "academic" information evaluation skills to their everyday life information seeking, thus suggesting the need for improved and updated information literacy instruction that is more broadly applicable to people's everyday life information needs.